Values of Character Education in Dampeng Dance at Wedding Ceremonies of the Subulussalam Community - Retno Dumilah; Azizah Hanum OK; Yusnaili Budianti (Journal of Educational Sciences, 2026)
This study research explores the importance of preserving local cultural values that embody character education, particularly within traditional performing arts such as the Dampeng Dance. This dance is an integral part of wedding ceremonies in the community of Subulussalam City and carries deep symbolic and ethical meanings. The objective of this study is to identify and analyze the character education values embedded in the Dampeng Dance and to assess their relevance to community life. A qualitative approach with a descriptive-analytical method was employed in this research. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that the Dampeng Dance contains character values such as cooperation, responsibility, religiosity, courtesy, and respect for ancestral traditions. These values are reflected in the dance movements, costumes, accompanying music, and the context of its performance within traditional ceremonies. The conclusion of this study affirms that the Dampeng Dance functions not only as a form of entertainment or aesthetic expression but also as an educational medium for instilling and preserving character education values among the people of Subulussalam across generations.